Convergence between satellite information and farmers' perception of drought in rangelands of North-West Patagonia, Argentina. (September 2020) - Solano-Hernandez, A.; Bruzzone, O.; Groot, J.; Laborda, L.; Martínez, A.; Tittonell, P.; Easdale, M.H.
Highlights: Drought is a complex natural hazard with social and environmental implications. The integration of local and scientific knowledge is lacking in drought monitoring and early warning systems. We assessed the degree of convergence between satellite-sensed information and farmers' perception of drought. Satellite information matched farmers' perception of drought at a regional scale, with partial matches at local scales. There is a need for knowledge integration for the development of drought monitoring and early warning systems at finer scales. Abstract: Drought is a complex natural hazard with social and environmental implications. Satellite information is increasingly used to support decision-makers in preventing or coping with the negative impacts of drought. The integration of local and scientific knowledge to support drought monitoring is still far from being the main procedure in the development of drought monitoring and early warning systems. This study aimed at assessing the degree of convergence between satellite information on the effect of droughts on rangeland vegetation, from time series analysis, and farmers' perception of drought in North-West Patagonia, Argentina. We characterised the scientific evidence of drought in terms of duration, spatial distribution, most severe years and recovery for the period 2000–2018 by identifying inter-annual NDVI changes. Farmers' perceptions and experiences of drought were studied with open-ending interviews, with respect to occurrence, duration and recovery for that period. Satellite information matched farmers' perception of drought at a regional scale, emphasising the value of remote sensing tools in supporting regional policy decision-making. However, farmers' perceptions and recall of past drought impacts were more diverse than satellite information at a local level, highlighting the need for knowledge integration at finer scales.